2019
DOI: 10.1002/bsl.2391
|View full text |Cite
|
Sign up to set email alerts
|

Can empathy close the racial divide and gender gap in death penalty support?

Abstract: Public opinion data indicate that the majority of US respondents support the death penalty. Research has consistently indicated, however, that Blacks and females are significantly less likely to support capital punishment than their White and male counterparts. Past research efforts attempting to account for these differences have, at best, only partially accounted for them: the racial divide and gender gap in death penalty support, while narrowed, remained evident. This study proposes that empathy, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
(144 reference statements)
2
12
0
Order By: Relevance
“…These policies were not explicitly racial as asked. Note that the care/harm moral foundation did reduce support for the death penalty in line with research showing that empathy and similar factors manifest this association (see, e.g., Applegate et al, 2000;Godcharles et al, 2019;Unnever & Cullen, 2007a;Unnever, Cullen, & Applegate, 2005, Unnever et al, 2006Unnever, Cullen, & Fisher, 2005). By contrast, even with significant effects found for racial resentment, care/harm, and egalitarianism, the analysis revealed that racial sympathy heightened perceptions that the death penalty was racially discriminatory.…”
Section: Effects Of Racial Sympathysupporting
confidence: 65%
See 2 more Smart Citations
“…These policies were not explicitly racial as asked. Note that the care/harm moral foundation did reduce support for the death penalty in line with research showing that empathy and similar factors manifest this association (see, e.g., Applegate et al, 2000;Godcharles et al, 2019;Unnever & Cullen, 2007a;Unnever, Cullen, & Applegate, 2005, Unnever et al, 2006Unnever, Cullen, & Fisher, 2005). By contrast, even with significant effects found for racial resentment, care/harm, and egalitarianism, the analysis revealed that racial sympathy heightened perceptions that the death penalty was racially discriminatory.…”
Section: Effects Of Racial Sympathysupporting
confidence: 65%
“…Finally, an obvious concern is that any effects attributed to racial sympathy might be due to respondents holding a global orientation for caring for others. As noted, prior studies have, in fact, reported that constructs such as compassion, empathy, and religious forgiveness decrease punitiveness, including support for the death penalty (Applegate et al, 2000;Godcharles et al, 2019;Metcalfe et al, 2015;Unnever & Cullen, 2007a;Unnever, Cullen, & Applegate, 2005;Unnever et al, 2006;Unnever, Cullen, & Fisher, 2005). To address this issue, the analysis includes a measure of "care/harm," one of the five foundations of morality identified by Haidt (2012).…”
Section: Research Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…She demonstrates as well that such sympathy diminishes punitiveness toward Black offenders. Although limited, research in criminology shows that orientations such as compassion, empathy, and religious forgiveness are related to less support for capital punishment and to lower levels of punitiveness (see, e.g., Applegate, Cullen, Fisher, & Vander Ven, 2000;Godcharles, Rad, Heide, Cochran, & Solomon, 2019;Metcalfe, Pickett, & Mancini, 2015;Unnever & Cullen, 2007a;Unnever, Cullen, & Applegate, 2005, Unnever, Cullen, & Bartkowski, 2006Unnever, Cullen, & Fisher, 2005). More generally in the social sciences, a call exists to explore a range of racial views, including Whites' racial apathy (Brown, Bento, Gorman, Koku, & Culber, 2019;Forman & Lewis, 2006) and racial emotions (Bonilla-Silva, 2019).…”
mentioning
confidence: 99%
“…Ethnocultural empathy (Wang et al, 2003) is one of the more commonly used indicators of empathic attitudes towards People of Color in general; a number of researchers view ethnocultural empathy as a disposition amenable to change over the course of time (Fleming, Thomas, Shaw, Burnham, & Charles, 2015). Research suggests ethnocultural empathy is associated with increased positive intergroup relations (Chapman et al, 2018;Peifer, Lawrence, Williams, & Leyton-Armakan, 2016) as well as attitudes toward controversial race-related topics such as the death penalty (Godcharles, Rad, Heide, Cochran, & Solomon, 2019). Conceptually, greater empathic feelings toward racial minority groups should be linked to greater emotional responding or concern regarding Trayvon Martin's shooting and Zimmerman's acquittal.…”
Section: Ethnocultural Empathymentioning
confidence: 99%